2015
DOI: 10.1007/s00779-015-0893-5
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating peripheral interaction: design and evaluation of peripheral interaction for a gesture-based lighting control with multimodal feedback

Abstract: Most interactions with today's interfaces require a person's full and focused attention. To alleviate the potential clutter of focal information, we investigated how interactions could be designed to take place in the background or periphery of attention. This paper explores whether gestural, multimodal interaction styles of an interactive light system allow for this. A study compared the performance of interactions with the light system in two conditions: the central condition in which participants interacted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 44 publications
0
4
0
1
Order By: Relevance
“…Visual attention is a measure used in driving studies [24,11,33] to evaluate the amount of distraction caused by secondary tasks. Liang et al [19] have shown that duration of glances reliably predicts the risk of crashes.…”
Section: Related Workmentioning
confidence: 99%
“…Visual attention is a measure used in driving studies [24,11,33] to evaluate the amount of distraction caused by secondary tasks. Liang et al [19] have shown that duration of glances reliably predicts the risk of crashes.…”
Section: Related Workmentioning
confidence: 99%
“…One example is a gestural light controller, based on a laser pointer, and a light sensor mounted on the lamp to identify when the lamp was addressed, inside a small handheld unit which contained various sensors and actuators. The research project looked at ambient or peripheral interaction, and participants were tested in a controlled study with varying feedback modalities (visual, auditory, and haptic) to show that they were able to control light levels accurately as a peripheral task when occupied in a focal task simultaneously, significantly better (increased speed and accuracy of the interaction) with the multimodal confirmation and articulatory feedback (Heijboer et al 2016).…”
Section: Conclusion and Further Researchmentioning
confidence: 99%
“…Heijboer et, al. [7] resaltaron que el puntero de luz es un dispositivo adecuado para estudiar la viabilidad de las interacciones periféricas con una interfaz gestual. El objetivo de este experimento exploratorio fue rediseñar los estilos de interacción del puntero de luz de tal manera que potencialmente podría interactuar con la periferia de la atención.…”
Section: Trabajos Relacionadosunclassified